NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN : (KAJIAN TAFSIR AL-QUR’AN SURAH AL-BAQARAH AYAT 261-267) - Balkis Azizah; Hadziq Zubad Ridla; Zainal Arifin (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2023)
The phenomenon of character crisis is being intensively experienced by various age levels, which has an uneasy impact on society. Given that the Al-Quran is the source of all problematic answers, Q.S al-Baqarah verses 261-267 is one of the solutions to the character crisis as well as the cultivation and application of good character education, which has religious, personal, and social values. This research uses qualitative research with the type of library research. Meanwhile, the object of this research is Al-Qur'anul Karim. In conducting research, data collection techniques are carried out by collecting and classifying data; the final stage is grouping it according to the theory used. The results of the study show that the values ??of character education contained in Q.S Al-Baqarah verses 261-267 are: (1) religious character values ??, which include spending wealth in the way of Allah, wisdom from spending wealth in the way of Allah and regarding the prohibition of riya'; (2) the personal character values ??contained in the six verses are habitual and generous; and (3) three values ??of social care character were found, namely maintaining speech, caring to give the best that one has.